RDONet: Rate-Distortion Optimized Learned Image Compression with Variable Depth - Brand, Fabian; Fischer, Kristian; Kopte, Alexander; Windsheimer, Marc; Kaup, André (IEEE Computer Society Conference on Computer Vision and Pattern Recognition Workshops, 2022)
Rate-distortion optimization (RDO) is responsible for large gains in image and video compression. While RDO is a standard tool in traditional image and video coding, it is not yet widely used in novel end-to-end trained neural methods. The major reason is that the decoding function is trained once and does not have free parameters. In this paper, we present RDONet, a network containing state-of-the-art components, which is perceptually optimized and capable of rate-distortion optimization. With this network, we are able to outperform VVC Intra on MS-SSIM and two different perceptual LPIPS metrics. This paper is part of the CLIC challenge, where we participate under the team name RDONet FAU.
CRIS-Team Scopus Importer:2022-09-30